The Implicit Keller Box Scheme for Combined Heat and Mass Transfer of Brinkman‐Type Micropolar Nanofluid with Brownian Motion and Thermophoretic Effect Over an Inclined Surface - Rafique, Khuram; Anwar, Muhammad Imran; Misiran, Masnita; Khan, Ilyas; M. Sherif, El-Sayed (MDPI, 2020)
The main purpose of the present analysis is to report the numerical solution of the thermal radiations and magnetohydrodynamic (MHD) effect on the flow of micropolar nanofluid. Further, the effect of Brownian motion and thermophoresis on the flow field are also elucidated. The combined phenomenon of heat and mass transfer is considered. Compatible similarities are implemented for the conversion of nonlinear ordinary differential equations from nonlinear partial differential equations. The numerical solution of the governing differential equations is obtained via the implicit Keller box technique. This is an efficient scheme based on the finite difference method. Findings demonstrate that the heat and mass exchange reduce with growth of the Brinkman parameter, whereas the wall shear stress enhances with improving the magnitude of the Brinkman factor. The temperature contour enhances when the radiation parameter reaches its peak, which is useful for industrial processes. The heat and mass flow rates decrease against higher magnitudes of inclination